Physiological Responses of Juvenile Barramundi (Lates calcarifer) Fed Processed Animal Protein Diets - Siddik, Muhammad Abu Bakar (Curtin University, 2018)
The research investigated the effectiveness of proteins from tuna hydrolysate (TH) and poultry by product meal (PBM), as fishmeal (FM) protein replacements. The results demonstrated that replacement of 10% FM with TH improved growth, immunity, intestinal health and disease resistance in juvenile barramundi. The addition of 10% TH in bioprocessed PBM not only improved the physiology of the fish but also increased the fish growth when 100% fishmeal protein was replaced by PBM protein.